Tanggungjawab PPAT pengganti terhadap surat kuasa membebankan hak tanggungan berobjek izin membuka tanah negara - Dinne Diaren Dizan; Iwan Permadi; Hariyanto Susilo (Jurnal Cakrawala Hukum, 2021)
Permit to open state land based on the Regional Regulation of the City of Balikpapan Number 1 of 2014 concerning State Land Opening Permits is not an object of Mortgage Rights, objects of mortgage rights are land rights that have the status of Property Rights, Business Use Rights, Building Use Rights and Use Rights over state land as described in Article 51 UUPA in conjunction with Article 4 of the Mortgage Rights Law. Since the State Land Opening Permit is not an object of mortgage rights, it is actually not justified if the state land is pledged as repayment of debtor's debt which is bound by an Authorisation for Assignment of Mortgage  IMTN objects as collateral are risky when the debtor is in default. Normative juridical research is a type of research used in this study while using a statutory approach and a conceptual approach. Research results Inclusion of IMTN objects in SKMHT is not in accordance with the applicable Prevailing Laws. SKMHT that is not in accordance with the provisions of the Mortgage Rights Law, UUPA, and the provisions of the terms of the authenticity of a deed can result in being null and void. The responsibility of the Substitute PPAT is the same as the PPAT, namely personally for the implementation of his / her job duties as well as the PPAT in accordance with Article 41 paragraph (7) of Perkaban No.1 of 2006.How to cite item: Dizan, D., Permadi, I., Susilo, H. (2021). Tanggungjawab PPAT pengganti terhadap surat kuasa membebankan hak tanggungan berobjek izin membuka tanah negara. Jurnal Cakrawala Hukum, 12(3), 263-273. doi:https://doi.org/10.26905/idjch.v12i3.4966.